Simulation and verification of electronic and biological systems - Li, Pen; Silveira, Luís Miguel; Feldmann, Peter; SpringerLink (Online service). (Dordrecht Springer, 2011)
Simulation and Verification of Electronic and Biological Systems provides a showcase for the Circuit and Multi-Domain Simulation Workshop held in San Jose, California, USA, on November 5, 2009. The nine chapters are contributed by experts in the field and provide a broad discussion of recent developments on simulation, modeling and verification of integrated circuits and biological systems. Specific topics include large scale parallel circuit simulation, industrial practice of fast SPICE simulation, structure-preserving model order reduction of interconnects, advanced simulation techniques for oscillator networks, dynamic stability of static memories and biological systems as well as verification of analog integrated circuits. Simulation and verification are fundamental enablers for understanding, analyzing and designing an extremely broad range of engineering and biological circuits and systems.  The design of nanometer integrated electronic systems and emerging biomedical applications have stimulated the development of novel simulation and verification techniques and methodologies. Simulation and Verification of Electronic and Biological Systems provides a broad discussion of recent advances on simulation, modeling and verification of integrated circuits and biological systems and offers a basis for stimulating new innovations
Forward. Preface -- List of Contributors -- Parallel Transistor-Level Circuit Simulation; Eric R. Keiter, et al. A Perspective on Fast-SPICE Simulation Technology; Michał Rewieński -- Recent Advances in Structure-Preserving Model Order Reduction; Roland W. Freund -- Injection Locking Analysis and Simulation of Weakly Coupled Oscillator Networks; Prateek Bhansali and Jaijeet Roychowdhury -- Dynamic Stability of Static Memories: Concepts and Advanced Numerical Analysis Techniques; Peng Li, et al. Recycling Circuit Simulation Techniques for Mass-Action Biochemical Kinetics; Jared Toettcher, et al. Circuit-based Models of Biomolecular System Dynamics; Elebeoba E. May -- Analog Verification; Ken Kundert and Henry Chang -- Formal Methods for Verification of Analog Circuits; Sebastian Steinhorst and Lars Hedrich
Selected conference papers presented at the Circuit and Multi-Domain Simulation Workshop held in San Jose, California, on November 5, 2009
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Integrated circuits -- Verification -- Congresses; Integrated circuits -- Computer simulation -- Congresses; Nanoelectronics -- Congresses